Long-term safety of siltuximab in patients with idiopathic multicentric Castleman disease: a prespecified, open-label, extension analysis of two trials. Issue 3 (March 2020) - van Rhee, Frits; Casper, Corey; Voorhees, Peter M; Fayad, Luis E; Gibson, Damilola; Kanhai, Karan; Kurzrock, Razelle
Summary: Background: Siltuximab is recommended by international consensus as a first-line treatment for idiopathic multicentric Castleman disease on the basis of durable efficacy and safety data. This study was done to assess the long-term safety and activity of siltuximab over up to 6 years of treatment. Methods: This study is a prespecified open-label extension analysis of a phase 1 trial (NCT00412321 ) and a phase 2 trial (NCT01024036 ), done at 26 hospitals worldwide. Patients in both studies were at least 18 years old with histologically confirmed, symptomatic Castleman disease. This extension study enrolled 60 patients who completed the previous trials without disease progression on siltuximab. Patients received siltuximab infusions of 11 mg/kg every 3 weeks (which could be extended to 6 weeks) for up to 6 years. Descriptive statistics were used to summarise the data. No formal hypothesis testing was performed. The primary endpoint was the safety of siltuximab, assessed at each dosing cycle. The study was registered with ClinicalTrials.gov, number NCT01400503 and with EudraCT, number 2010-022837-27. Findings: Patient enrolment into the phase 1 trial was from June 20, 2005, to Sept 15, 2009, and enrolment into the phase 2 trial was from Feb 9, 2010, to Feb 3, 2012. Patients were enrolled in this long-term extension from April 1, 2011, to Jan 15, 2014. Median follow-up was 6 years (IQR 5·11–7·76). Median treatment duration, from the beginning of the previous trials to the end of the present study, was 5·5 years (IQR 4·26–7·14). Siltuximab was well tolerated; however, adverse events of grade 3 or worse were reported in 36 (60%) of 60 patients with the most common being hypertension (eight [13%]), fatigue (five [8%]), nausea (four [7%]), neutropenia (four [7%]), and vomiting (three [5%]). 25 (42%) patients reported at least one serious adverse event, which most commonly was an infection (eight [13%]). Only two serious adverse events, polycythaemia and urinary retention, were considered related to siltuximab treatment. 18 patients discontinued before study completion, either to receive siltuximab locally (eight) or because of progressive disease (two), adverse events (two), or other reasons (six). No deaths were reported. Interpretation: These results show that siltuximab is well tolerated long term and provides important evidence for the feasibility of the life-long use required by patients with idiopathic multicentric Castleman disease. Funding: Janssen R&D and EUSA Pharma.